Experimental characterisation of WiMAX propagation in different environments - Robalo, Daniel Luís Silveira (2011)
The aim of this work is to continue the cooperation on Fixed WiMAX experimental propagation characterization between Instituto de Telecomunicações - DEM of University of Beira Interior, Portugal, Fondazione Ugo Bordoni and the Department of Electronics and Information Systems of the University of Bologna, both from Italy. The field trials addressed different environments, i.e., suburban and open areas in a hilly terrain for the study of the propagation characteristics of WiMAX systems. The IEEE 802.16-2004 equipment operates at 3.5 GHz with a bandwidth of 3.5 MHz. Different antenna heights are considered. The measurements have been performed in outdoor, indoor and mixed environments, with omnidirectional and 120° sectored antennas. In the outdoor environment, results show an adequacy between the trend-curve for the experimental results with the modified Friis equation with propagation exponent 2.71.